Estabilização de blocos de terra crua através de ativação alcalina - Oliveira , Leandro Santos de (2015)
Stabilization is important in earthen construction in order to improve mechanical strength, volumetric stability, workability and even ductility. Currently, the products used to stabilize the earth are lime, Portland cement and bitumen emulsions. Due to the environmental problems that the mankind faces nowadays, the use of earthen construction is increasing. Adobe is the most traditional type of block used in masonry. To improve strength against water, a new way to stabilize this kind of unburned earth block is proposed by the alkaline activation of earth. This paper presents the first results about the experimentation made in the stabilization of soil with alkali activator. Two cure temperatures were tested: room temperature and oven at 50ºC. The amounts of stabilizer used were 3% and 6% activator by mass of earth. Results show that it is possible for adobe blocks to be resistant to compression and water action using the alkaline activation.